Fragmentation of the Sinai Plate indicated by spatial variation in present-day slip rate along the Dead Sea Fault System. Issue 3 (27th February 2020) - Gomez, Francisco; Cochran, William J; Yassminh, Rayan; Jaafar, Rani; Reilinger, Robert; Floyd, Mike; King, Robert W; Barazangi, Muawia
SUMMARY: A comprehensive GPS velocity field along the Dead Sea Fault System (DSFS) provides new constraints on along-strike variations of near-transform crustal deformation along this plate boundary, and internal deformation of the Sinai and Arabian plates. In general, geodetically derived slip rates decrease northwards along the transform (5.0 ± 0.2 to 2.2 ± 0.5 mm yr −1 ) and are consistent with geological slip rates averaged over longer time periods. Localized reductions in slip rate occur where the Sinai Plate is in ∼N–S extension. Extension is confined to the Sinai side of the fault and is associated with prominent changes in transform geometry, and with NW–SE striking, left-lateral splay faults, including the Carmel Fault in Israel and the Roum Fault in Lebanon. The asymmetry of the extensional velocity gradients about the transform reflects active fragmentation of the Sinai Plate along the continental margin. Additionally, elastic block modelling of GPS velocities requires an additional structure off-shore the northern DSF segment, which may correspond with a fault located along the continental margin, suggested by prior geophysical studies.